Comparative study on seismic vulnerability of RC bridge piers reinforced with normal and high-strength steel bars. (February 2021) - Su, Junsheng; Li, Zhong-Xian; Prasad Dhakal, Rajesh; Li, Chao; Wang, Fangbo
Abstract: Use of high-strength steel bars (HSSB) in RC bridge piers reduces the amount of reinforcement or enhances bearing capacity of RC piers. However, the use of HSSB could come with reduction in the energy dissipation of RC member, which used to be considered detrimental to the seismic performance of RC bridge piers. This paper revaluates the effects of HSSB on seismic performance of RC piers by comparing that with normal steel bars (NSB) through fragility analysis. Maximum drift ratio (MDR) and maximum section curvature (φm ) are considered as engineering demand parameters (EDPs) to represent the deformation demands and section damage of RC piers, respectively. A fiber-based finite element model (FEM), calibrated by a set of shaking table tests of RC portal frames reinforced with NSB and HSSB, is adopted to simulate the nonlinear dynamic response of RC piers. Fragility curves using probabilistic seismic demand model (PSDM) are developed to compare the relative vulnerability of RC bridge piers reinforced with steel of different yield strengths. The analysis results indicate that, when using HSSB to replace NSB by equal volume replacement, the RC piers have similar deformation demands (MDR) but significantly less section damage. On the other hand, when using HSSB to replace NSB by equal strength replacement, the deformation demands (MDR) of RC piers slightly increase (about 5%) due to the decrease of post-cracking stiffness under small reinforcement ratio. In spite of slight increase of deformation demands, the use of HSSB by equal strength replacement still reduces RC piers' section damage since the use of HSSB enhances the elastic deformation and then reduces the plastic deformation of RC piers. Moreover, as elastic deformation accounts for a higher proportion of total deformation for taller piers, the reduction amplitudes of section damage are more evident when using HSSB in taller piers. On the whole, the application of HSSB to replace NSB is more likely to be beneficial to the seismic performance of RC piers.